2017
DOI: 10.3390/inorganics5040071
|View full text |Cite
|
Sign up to set email alerts
|

Unique Hydrogen Desorption Properties of LiAlH4/h-BN Composites

Abstract: Hexagonal boron nitride (h-BN) is known as an effective additive to improve the hydrogen de/absorption properties of hydrogen storage materials consisting of light elements. Herein, we report the unique hydrogen desorption properties of LiAlH 4 /h-BN composites, which were prepared by ball-milling. The desorption profiles of the composite indicated the decrease of melting temperature of LiAlH 4 , the delay of desorption kinetics in the first step, and the enhancement of the kinetics in the second step, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…As shown in Figure (a), a 40% h-BN composite after milling showed the presence of Al and N throughout the particle. As shown in a previous study, LiAlH 4 was confirmed in the XRD profile . In the STEM analysis, it was difficult to observe diffraction spots from LiAlH 4 because of LiAlH 4 decomposition by an electron beam.…”
Section: Results and Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…As shown in Figure (a), a 40% h-BN composite after milling showed the presence of Al and N throughout the particle. As shown in a previous study, LiAlH 4 was confirmed in the XRD profile . In the STEM analysis, it was difficult to observe diffraction spots from LiAlH 4 because of LiAlH 4 decomposition by an electron beam.…”
Section: Results and Discussionsupporting
confidence: 56%
“…Li 3 AlH 6 formation was confirmed in the LiAlH 4 /h-BN composite. 19 As shown in the NMR spectrum in Figure 7(c), the LiBH 4 peak was also observed in the h-BN composite. The relative intensity of LiBH 4 peak in t-BN composite was stronger than that in h-BN composite, indicating that a large amount of LiBH 4 phase was formed in the t-BN composite.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…However, aluminium-based complex hydrides were the first complex hydrides to be successfully catalysed. Nakagawa, Isobe, Ohki and Hashimoto recently investigated new types of additive effects of ball milled lithium alanate with hexagonal boron nitride, LiAlH 4 −h-BN [18]. The role of h-BN on the desorption process of LiAlH 4 was discussed in comparison with the desorption properties of LiAlH 4 −X (X = graphite, LiCl or LiI) [18].…”
mentioning
confidence: 99%